Visual imagination and the narrative image. Parallelisms between art history and neuroscience. (August 2018) - Horváth, Gyöngyvér
Abstract: Understanding visually presented stories requires intense effort from our visual imagination. Artists and theoreticians from the Renaissance onwards suggested various ways to depict stories, either to enhance their understanding and enjoyment, or to help adjust the depictions to the aesthetic ideas of the era. Alberti's concept of istoria, Leonardo's practice of visual stimulation, Lessing's advice on how to choose the most fruitful moment of a story relied both on personal experience and the scientific knowledge of the era. Visual imagination is specially needed in non-figurative and sequential narratives in modern and contemporary art, which are supported by Arnheim's notion of stroboscopic motion. Recent developments in image-making technologies enable some clarification of the processes involved in human perception with regard to the understanding of painted scenes and visually presented stories. The objective of this paper is to find the counterparts of these art theoretical concepts in psychology and neuroscience. Through the phenomena of mirror neurons, scene perception, gist of scene, and face and object recognition, these findings establish parallelisms between art history and neuroscience.